Punishments and rewards both modestly impair visuomotor memory retention - Hamel, R.; De La Fontaine, É.; Lepage, J.F.; Bernier, P.M. (Neurobiology of learning and memory, 2021)
While the effects of rewards on memory appear well documented, the effects of punishments remain uncertain. Based on neuroimaging data, this study tested the hypothesis that, as compared to a neutral condition, a context allowing successful punishment avoidance would enhance memory to a similar extent as rewards. In a fully within-subject and counter-balanced design, participants (n = 18) took part in 3 distinct learning sessions during which the delivery of performance-contingent monetary punishments and rewards was manipulated. Specifically, participants had to reach towards visual targets while compensating for a gradually introduced visual deviation. Accuracy at achieving targets was either punished (Hit: “+0$”; Miss: “−0.5$), rewarded (Hit: “+0.5$”; Miss: “−0$”), or associated with neutral binary feedback (Hit: “Hit”; Miss: “Miss”). Retention was assessed through reach aftereffects both immediately and 24 h after initial acquisition. The results disconfirmed the hypothesis by showing that the punishment and reward learning sessions both impaired retention as compared to the neutral session, suggesting that both types of incentives similarly impaired memory formation and consolidation. Two alternative but complementary interpretations are discussed. One interpretation is that the presence of punishments and rewards induced a negative learning context, which – based on neurobiological data – could have been sufficient to interfere with memory formation and consolidation. Another interpretation is that punishments and rewards emphasized the disrupting effects of target hits on implicit learning processes, therefore yielding retention impairments. Altogether, these results suggest that incentives can have counter-productive effects on memory.